Changes in the physicochemical and protein distribution properties of dough with the wheat oligopeptide incorporation. (April 2023) - Liu, Hongyan; Wan, Liuyu; Xiao, Shensheng; Fu, Yang; Wang, Xuedong
Abstract: The characteristics of the dough modification are crucial to the quality of the final product. This study aimed to investigate the effects of wheat oligopeptide (WOP) on dough rheology, physicochemical, and protein distribution properties. Rheological results showed that WOP increased the viscoelasticity, extensibility, and strength of the dough. The pasting experiments illustrated that WOP decreased the peak viscosity, breakdown, and setback values. The fermentation results showed that WOP significantly increased the fermentation height and gas-holding rate of the dough. Meanwhile, the water migration ability of the dough was significantly inhibited after WOP incorporation. Furthermore, the electrophoresis results further proved that WOP could effectively enhance the aggregation of small molecule proteins. The microstructure results further demonstrated that the dough exhibited more uniform and continuous characteristics with the WOP incorporation, which was consistent with our hypothesis. In conclusion, WOP has the ability to strengthen the dough network structure, providing a new idea for future modification of dough and its products. Graphical abstract: Image 1 Highlights: Wheat oligopeptide (WOP) inhibited the pasting properties. WOP promoted the dough stability and fermentation volume. WOP promoted the aggregation of gluten proteins to form a denser network.